Education Fever and Other Academic-Related Illnesses as Diagnosed by the Thai Movie “Bad Genius” - Inero V. Ancho; Genevie-Abi M. Calimbahin; Margie Mae E. Basal; Windy Rose M. Dela Rosa (Thai Journal of East Asian Studies, 2020)
Poverty, politics, and even education issues are typical disputes highlighted in movies. Storylines particularly revolve around a student or teacher’s daily struggle in school, or a flawed education system. By employing a content-based movie analysis, the movie Bad Genius is scrutinized and themes are presented according to established research objectives. Five major education issues are identified in this study: corruption, high stakes testing, academic pressure, education equity, and academic dishonesty. The movie is an attempt to document seemingly ignored societal cancers in our very own classrooms that breed worse and serious wounds. The movie serves as a gentle reminder in rekindling value and values education among students. It is about time to revisit school curricula and academic programs as the race to make it to the top becomes competitive and challenging.